THE CONCEPT OF POWER IN DELEUZE GUATTARI THOUGHT. PHILOSOPHICAL CONTRIBUTIONS TO CONTEMPORARY SOCIAL THEORY - Díaz, Germán Alejandro (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2015)
The aim of this paper is to light up some possible contribution that deleuzean philosophy could give to political and social theories. This is done by an examination of Deleuze’s conception of power. The first result of our research is the claim that this kind of examination requires a methodological reduction: from the pair of concepts  “molar” and “molecular” -on which is based deleuzean more general conceptions of society- to the pair “virtual” and “actual” or “event” and “state of things”. By the mentioned reduction it will be possible to identify two different and chronologically consecutive concepts of power, where the last one, which partially includes the first of them, allows to define power as an (non subjective) agent in production of subjectivity. The major contribution of this paper is precisely to identify and clear up this definition.